NILAI-NILAI TRADISI SEBAGAI INSPIRASI PENGEMBANGAN DESAIN KRIYA KONTEMPORER - Martono - (Imaji, 2010)
The development of modern skill design is continuously higher alongside with the development of science, technology, and human need. Long time ago, empu or male salesclerks made skill products which contained sacred values and other values. Now, they make skill products by considering more on their aspects of function, economic, and estetics. The shift of those values are caused by the development of science, the transition of human need, and the change of era demand. Global issue has created tension between tradition and modernity, global versus local, universal and individual, and preservation versus renewal. The condition of culture, which comes from the meet of two values of every single aspect, finally creates some tension between things which are considered spiritual and material by nature. Globalization has influenced the shift of art that is spiritual and symbolic by nature into art which is simply material by nature. The work of art is more oriented on the fulfillment of practical demand which is based on economical demand. The fast development of globalization process becomes a big problem for many skill designers, who are in one side have no willingness to relief beautiful and philosophical traditional art. Meanwhile, in another side, they realize that they can do nothing if they do not follow the global current in which the impact cannot be avoided. The development of tourism directly claims the skill designers to make some modern skill designs which have special context regarding the places where the designs are created and stereotype according to local culture of the places. Related to the development of tourism, there is a skill design that is especially dedicated to society; this skill design is known as art by destination. Additionally, a skill design for tourism society demand is called art of acculturation. Art which is created for the sake of tourism art demand is known as tourist art. The development of tourism has given a big chance toward the development of skill in Indonesia. It can be proven by a large number of skill design products which have spread locally and globally. Most of those skill products of various material and designs have come into export markets. It proves that skill and creativity of skill designers have been highly reliable and acceptable.